„Spitamegeranomachia” Jana Achacego Kmity - edycja księgi pierwszej - Aleksandra Goszczyńska (Meluzyna: dawna literatura i kultura, 2017)
The study is an attempt of a contemporary edition of the the first volume of “Spitamegeranomachia” by Jan Achacy Kmita (the second volume in preparation). It is related to the article Zaplecze inwencyjne „Spitamegeranomachii” Jana Achacego Kmity (The base for the ingeniousness of Jan Achacy Kmita’s “Spitamegeranomachia”) which may be regarded as an introduction into the current edition. Published in 1595, “Spitamegeranomachia” is the first Polish heroicomical poem which has been so far republished only once in 1897 in the collection of J. Stoka, M. Pudłowskiego i J.A. Kmity powieści wierszowane 1564–1610 (The verse-written stories by J. Stok, M. Pudłowski and J.A. Kmita (1564-1610). This Edition duplicated certain errors from the original publishing and apart from a glossary it offered no other explanations necessary in the case of a work having such a great number of allusions (paradoxographic, literature-historical and political references). This study aims at preparation of a modern transcription and, first of all, generation of a wider editing comment which would take into account numerous sources of the author’s invention. The issue is comprised of a short introduction, source description (original printing of 1595), critical apparatus and rules of transcription for the whole work, transcription of the dedication poem and the first volume of the narrative poem, as well as further explanations.